ANALISIS STRATEGI BERSAING PT HUAWEI TECH BERDASARKAN DAYA TARIK INDUSTRI DAN ANALISIS RANTAI NILAI - , Friska Lidia; , dr. Rangga Almahendra, S.T., MM. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The development of market-leading mobile phone or wireless service in Indonesia is growing increasingly vibrant along with the growing market demand for mobile or wireless telecommunication services, which not only happened in urban yet to remote areas. Total market share of the telecommunications industry continues to increase. The company is currently facing vendor competition is very tight so it must find a way to survive and continue to grow to face its competitors. Competition is extremely tight in the field of telecommunications is spurring vendors to continue to internal and external evaluation and determine the company's competitive advantage to continue to react to the market. In general, PT Huawei actually has many advantages such as technology, finance and human resources is very supportive of business. But there are still weaknesses that the existence of the company is the brand image of the company itself. Based on the above problems, in this thesis will be the analysis of competition in the telecommunications business of PT Huawei in the form of research on external factors such as industry analysis and internal factors. From this analysis aimed at identifying opportunities, threats, strengths and weaknesses of PT Huawei, and gain a competitive advantage based on resources and capabilities of PT Huawei. From the results of the analysis focused on the formulation of competitive strategy to exploit the company's competitive advantage.